A 3D computational study of flow instability development due to driven cavity with a cylindrical shape at different locations. (16th February 2021) - Souayeh, Basma; Hammami, Fayçal
A numerical investigation has been carried out to study the two-sided lid-driven cubical cavity induced by a cylindrical shape at the centre. This problem is solved by a finite volume method using multigrid acceleration. The cavity has left and right parallel lid-driven walls and all the other walls completing the domain are motionless. Different locations of the inner cylinder along the centreline at left and right parts of the enclosure; [P1(0.3, 0.3), P2(0.7, 0.3), P3(0.7, 0.7) and P4(0.3, 0.7)] are employed encompassing descriptive Reynolds numbers ranging three orders of magnitude 100, 400 and 1000. The obtained results show that positions P3 and P4 of the inner cylinder promote cell distortion. Thereafter, the study has been extended to the unsteady state by further increasing Reynolds number till reaching 1500. It has been proved that a cylinder centrally located inside the enclosure promotes faster transition to the unsteadiness rather than the four considered locations.